Ultrastructural changes produced in the rat kidney by a mercurial diuretic (meralluride) - Sanabria, A. (1963)
Electron microscopic study of the cortical and medullary zones of kidneys of rats injected intraperitoneally with meralluride (a mercurial diuretic) shows that constant structural changes occur in the proximal tubules, but that the distal tubules remain unaltered. In the cells of the proximal tubule vacuolation and loss of contrast of the apical pole occur due to intracytoplasmic oedema, appearances which may extend as far as the basal pole. The brush border shows separation of the villi at the level of the implantation base. Mitochondrial swelling occurs with vacuolation of the matrix and disappearance of the cristae. The changes at the level of the glomerulus are variable and consist of clearing of the mitochondrial matrix of the podocytes, enlargement of the vesicles of the endoplasmic reticulum and the occurrence of intracytoplasmic osmiophilic masses.